Accuracy and bias in facial trustworthiness appraisals in borderline personality disorder - Miano, Annemarie; Lustig, Sophia; Meyerding, Luca; Barnow, Sven (Journal of personality disorders, 2023)
Individuals with borderline personality disorder (BPD) have shown a negativity bias, whereas the general population has shown a positivity bias in their trustworthiness appraisal of others. We tested if individuals with BPD are more negative but also more realistic with their appraisals. Trustworthiness was objectified on an external criterion. The influence of childhood trauma was investigated. Facial photographs of peace prize laureates and sentenced murderers were presented. Participants with BPD and healthy controls (HC) rated the trustworthiness of the targets. Bias and sensitivity were measured using signal detection theory. The BPD group was more negatively biased compared to HC, but not more sensitive in discriminating between the two groups. When correcting for experienced childhood abuse and neglect, the authors found that group differences in bias disappeared. Individuals with BPD might not be more sensitive in discriminating between, on average, more or less trustworthy targets, but they have developed a negativity bias to ensure the detection of untrustworthiness.